Pharmacological inhibition of PAI-1 alleviates cardiopulmonary pathologies induced by exposure to air pollutants PM2.5. (15th October 2021) - Ghosh, Asish K.; Soberanes, Saul; Lux, Elizabeth; Shang, Meng; Aillon, Raul Piseaux; Eren, Mesut; Budinger, G.R. Scott; Miyata, Toshio; Vaughan, Douglas E.
Abstract: Numerous studies have established that acute or chronic exposure to environmental pollutants like particulate matter (PM) leads to the development of accelerated aging related pathologies including pulmonary and cardiovascular diseases, and thus air pollution is one of the major global threats to human health. Air pollutant particulate matter 2.5 (PM2.5 )-induced cellular dysfunction impairs tissue homeostasis and causes vascular and cardiopulmonary damage. To test a hypothesis that elevated plasminogen activator inhibitor-1 (PAI-1) levels play a pivotal role in air pollutant-induced cardiopulmonary pathologies, we examined the efficacy of a drug-like novel inhibitor of PAI-1, TM5614, in treating PM2.5 -induced vascular and cardiopulmonary pathologies. Results from biochemical, histological, and immunohistochemical studies revealed that PM2.5 increases the circulating levels of PAI-1 and thrombin and that TM5614 treatment completely abrogates these effects in plasma. PM2.5 significantly augments the levels of pro-inflammatory cytokine interleukin-6 (IL-6) in bronchoalveolar lavage fluid (BALF), and this also can be reversed by TM5614, indicating its efficacy in amelioration of PM2.5 -induced increases in inflammatory and pro-thrombotic factors. TM5614 reduces PM2.5 -induced increased levels of inflammatory markers cluster of differentiation 107 b (Mac3) and phospho-signal transducer and activator of transcription-3 (pSTAT3), adhesion molecule vascular cell adhesion molecule 1 (VCAM1), and apoptotic marker cleaved caspase 3. Longer exposure to PM2.5 induces pulmonary and cardiac thrombosis, but TM5614 significantly ameliorates PM2.5 -induced vascular thrombosis. TM5614 also reduces PM2.5 -induced increased blood pressure and heart weight. In vitro cell culture studies revealed that PM2.5 induces the levels of PAI-1, type I collagen, fibronectin (Millipore), and sterol regulatory element binding protein-1 and 2 (SREBP-1 and SREBP-2), transcription factors that mediate profibrogenic signaling, in cardiac fibroblasts. TM5614 abrogated that stimulation, indicating that it may block PM2.5 -induced PAI-1 and profibrogenic signaling through suppression of SREBP-1 and 2. Furthermore, TM5614 blocked PM2.5 -mediated suppression of nuclear factor erythroid related factor 2 (Nrf2), a major antioxidant regulator, in cardiac fibroblasts. Pharmacological inhibition of PAI-1 with TM5614 is a promising therapeutic approach to control air pollutant PM2.5 -induced cardiopulmonary and vascular pathologies. Graphical abstract: Image 1 Highlights: Exposure to air pollutant PM2.5 causes accelerated cardiopulmonary pathologies. PM2.5 induces the levels of inflammatory, prothrombotic and profibrogenic PAI-1. PAI-1 inhibitor TM5614 reduced the level of PM2.5 -induced inflammatory markers. PAI-1 inhibitor TM5614 ameliorates PM2.5 -induced vascular thrombosis. TM5614 is a potential drug for therapy of PM2.5 -induced cardiopulmonary pathologies.